2018
DOI: 10.3390/ijms19051347
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Polyadenylation Signal of Pre-mRNA: A New Gene Silencing Approach for Facioscapulohumeral Dystrophy

Abstract: Facioscapulohumeral dystrophy (FSHD) is characterized by the contraction of the D4Z4 array located in the sub-telomeric region of the chromosome 4, leading to the aberrant expression of the DUX4 transcription factor and the mis-regulation of hundreds of genes. Several therapeutic strategies have been proposed among which the possibility to target the polyadenylation signal to silence the causative gene of the disease. Indeed, defects in mRNA polyadenylation leads to an alteration of the transcription terminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 153 publications
0
19
0
Order By: Relevance
“…SMCHD1 loss-of-function, D4Z4 hypomethylation and chromatin relaxation followed by activation of the DUX4 retrogene encoded by the last D4Z4 repeat and adjacent pLAM sequence is thought to be the driver mechanism in FSHD2 (Figure 6D). The DUX4 open reading frame is fully contained within the first exon encoded by D4Z4 whereas exons 2 and 3 corresponding to the DUX4 3′ untranslated region (3′ UTR) are encoded by the pLAM adjacent region (39). The main polyadenylation site (PAS) required for transcript stabilization and protein production is contained within exon 3 (Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMCHD1 loss-of-function, D4Z4 hypomethylation and chromatin relaxation followed by activation of the DUX4 retrogene encoded by the last D4Z4 repeat and adjacent pLAM sequence is thought to be the driver mechanism in FSHD2 (Figure 6D). The DUX4 open reading frame is fully contained within the first exon encoded by D4Z4 whereas exons 2 and 3 corresponding to the DUX4 3′ untranslated region (3′ UTR) are encoded by the pLAM adjacent region (39). The main polyadenylation site (PAS) required for transcript stabilization and protein production is contained within exon 3 (Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
“…The main polyadenylation site (PAS) required for transcript stabilization and protein production is contained within exon 3 (Figure 6D). Additional alternative polyadenylation sites have also been identified distal to the last repeat suggesting alternative site usage (39). Only the long DUX4 transcript ( DUX4-fl ) has been associated with FSHD.…”
Section: Resultsmentioning
confidence: 99%
“…During the past 10 years, several strategies aiming at inhibiting DUX4 expression have been developed (for review see [ 27 ]) and the poly(A) signal was already successfully targeted to inhibit DUX4 expression [ 19 , 21 ]. Targeting the key elements of DUX4 mRNA’s 3′UTR is attractive for several reasons: (i) correct polyadenylation of mRNAs is required for their stability, nuclear export and efficient translation, and targeting the polyadenylation signal can result in decreased gene expression (for review see [ 20 ]). (ii) DUX4 expression is common in FSHD1 and FSHD2 patients and therefore targeting DUX4 will be beneficial to all FSHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because we and others have previously shown that the use of antisense oligonucleotides targeting the 3′ end elements involved in DUX4 mRNA processing is an efficient therapeutic strategy for FSHD [ 19 , 20 , 21 , 22 ], in this study, we performed gene editing using transcription activator-like effector nuclease (TALEN) and CRISPR-Cas9 technology to permanently inhibit DUX4 expression by targeting its poly(A) signal sequence (PAS). Even though TALENs initially proved highly efficient nucleases for gene editing, CRISPR-Cas9 has now superseded TALEN technology due to the simplicity of designing guide RNAs for sequence-specific DNA cleavage by Cas9 proteins, the only constraint being the presence of a PAM motif, specific to the different Cas9 proteins available for gene editing, next to the target sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratories are developing therapeutic approaches targeting DUX4 by either blocking DUX4 mRNA synthesis [ 31 , 51 , 52 , 54 ], targeting DUX4 mRNA using antisense oligonucleotides [ 66 , 73 , 74 , 75 , 76 ], or targeting the DUX4 protein or its downstream consequences [ 77 , 78 , 79 ]. One phase 2 clinical trial (NCT04003974) aiming at inhibiting or reducing its expression in skeletal muscle is already on-going and may enable a better understanding of the role of DUX4 in the pathophysiology of FSHD.…”
Section: Discussionmentioning
confidence: 99%